APPLICATION OF MAMDANI FUZZY LOGIC IN REFRIGERATOR SELECTION - Oktarina, Anisa Dwi; Abadi, Agus Maman; Hamdi, Syukrul (PATTIMURA UNIVERSITY, 2025)
Refrigerators are essential household appliances that preserve food freshness and optimize storage efficiency. Selecting a refrigerator requires careful consideration of factors such as price, capacity, and electricity consumption. This research applies the Mamdani-type Fuzzy Inference System (FIS) to recommend refrigerators based on these three criteria. Using a dataset of 82 refrigerator brands, this study implements fuzzification, rule formation, inference, and defuzzification, supported by MATLAB software. The results indicate that refrigerators with a normal price, medium capacity, and low power consumption are the most suitable choices. Based on the dataset, the Aqua AQR-415IM model meets these criteria. While this study confirms the effectiveness of fuzzy logic in structured decision-making, it does not quantitatively measure efficiency. Future research should explore alternative fuzzy logic methods, incorporate additional input variables, and consider demographic factors to enhance recommendation accuracy. Additionally, the Mamdani method can be adapted for broader applications in selecting other electronic products, contributing to both practical consumer guidance and theoretical advancements in fuzzy logic-based decision support systems.